Neuroimmune Evasion of Zika Virus to Facilitate Viral Pathogenesis - Xie, Xiaochun; Zeng, Jianxiong (Frontiers in Cellular and Infection Microbiology, 2021)
Zika virus (ZIKV), which preferentially targets neural stem and progenitor cells (NSCs) especially in developing brain, is causally associated with fetal microcephaly, intrauterine retardation, and other congenital malformations in humans. However, there is, so far, no effective drugs and vaccines against ZIKV epidemics, warranting an enhanced understanding of ZIKV biology. Immune response is essential for neuronal cells to combat viral invasion. In turn, neurotropic ZIKV has developed a complex strategy of neuroimmune evasion to facilitate viral pathogenesis, especially developmental impairment in embryonic brain. Here, we review not only overall knowledge of ZIKV related immune responses, but also current advances in our understanding of immune evasion in ZIKV infection. We also review several specific mechanisms underlying ZIKV protein-mediated immune evasion for viral pathogenesis.